Faunistics of Coleoptera in subarctic pine forests in Finnish Lapland - Sippola, Anna-Liisa; Siitonen, Juha; Kallio, Reino (Entomologica Fennica, 1995)
The beetle fauna of pine forests was surveyed by window flight trapping in four separate study areas in Pallas-Ounastunturi National Park in Enontekiö Lapland (Le) and Hammastunturi wilderness area in Inari Lapland (Li). The total catch of individuals was 4905, consisting of 195 species. The proportion of species new to the province was 48% in Le and 25% in Li, respectively. Eleven rare species (known at most from 25 localities in Finland) were found. Rarefaction, diversity analyses and similarity indices showed that species richness, relative abundances of species and species composition did not differ significantly between the study areas.